Healthcare survey management system - Tai, Rebekah Shi Ting (Nanyang Technological University, 2020)
Technology has integrated into the health sector to improve patient experience and satisfaction. Electronic health as known as E-health has become a popular medium of data collection in the health sector as it allows valuable data to be gathered within a short period for various purposes.